2021
DOI: 10.3390/jpm11090875
|View full text |Cite
|
Sign up to set email alerts
|

Second-Generation 3D Automated Breast Ultrasonography (Prone ABUS) for Dense Breast Cancer Screening Integrated to Mammography: Effectiveness, Performance and Detection Rates

Abstract: In our study, we added a three-dimensional automated breast ultrasound (3D ABUS) to mammography to evaluate the performance and cancer detection rate of mammography alone or with the addition of 3D prone ABUS in women with dense breasts. Our prospective observational study was based on the screening of 1165 asymptomatic women with dense breasts who selected independent of risk factors. The results evaluated include the cancers detected between June 2017 and February 2019, and all surveys were subjected to a do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 50 publications
0
21
0
Order By: Relevance
“…ABUS includes computer-aided detection as auxiliary software, which can reduce the reading time without compromising the screening accuracy [ 35 , 36 ]. A study conducted in 2021 compared screening with MMG alone and with ABUS in 1165 women with dense breasts and reported that ABUS combined with MMG increased the sensitivity by 31.8% [ 37 ]. Future challenges include further examination of cost-effectiveness and, as with portable US (i.e., handheld US), reducing the risk of false positives [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…ABUS includes computer-aided detection as auxiliary software, which can reduce the reading time without compromising the screening accuracy [ 35 , 36 ]. A study conducted in 2021 compared screening with MMG alone and with ABUS in 1165 women with dense breasts and reported that ABUS combined with MMG increased the sensitivity by 31.8% [ 37 ]. Future challenges include further examination of cost-effectiveness and, as with portable US (i.e., handheld US), reducing the risk of false positives [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sensitivity increased significantly using both methods compared to applying solely a mammogram (63.6% vs. 100%) and specificity slightly decreased (99% vs. 98.4%) [18]. According to Gatta et al combing both methods are more accurate in the detection of breast cancer [19]. According to the results, 4 breast cancers were detected by the mammogram, whereas 8 were detected by applying a combination of both the…”
Section: Comparison Of Mammography and Abusmentioning
confidence: 98%
“…The specificity of the mammography was 94% and the combination of these two methods was 87%. The combination of these two methods provides a sensitivity level that is comparable to the MRI [19].…”
Section: Ap Projection Lateral Projection Medial Projectionmentioning
confidence: 99%
“…[36][37][38][39][40][41] Recent studies show that prone-based systems are promising for screening women with dense breasts with a diagnostic performance comparable to supine ABUS systems. 38 Furthermore, methods beyond conventional US, such as US-computed tomography (USCT), have been previously developed and shown useful for whole-breast 3D imaging. [42][43][44][45][46][47] Although ABUS-and 3DUS-based approaches use anatomical information to differentiate between fibroglandular (dense) tissues, benign and cancerous tissues, USCT provides quantitative measurements and simultaneous acquisition of 3D reflection, acoustic attenuation, and speed-of -sound images.…”
Section: Introductionmentioning
confidence: 99%
“…Alternative prone ABUS systems have been developed, including but not limited to, the commercially available SonixEmbrace™ (Ultrasonix Medical Corporation, British Columbia, Canada), SVARATM™ (TechniScan Inc., Utah, USA), and SOFIA™ (Hitachi Ltd, Tokyo, Japan) systems 36–41 . Recent studies show that prone‐based systems are promising for screening women with dense breasts with a diagnostic performance comparable to supine ABUS systems 38 . Furthermore, methods beyond conventional US, such as US‐computed tomography (USCT), have been previously developed and shown useful for whole‐breast 3D imaging 42–47 .…”
Section: Introductionmentioning
confidence: 99%